Biological sex is binary, even though there is a rainbow of sex roles: Denying biological sex is anthropocentric and promotes species chauvinism. (21st December 2022) - Goymann, Wolfgang; Brumm, Henrik; Kappeler, Peter M.
Abstract: Biomedical and social scientists are increasingly calling the biological sex into question, arguing that sex is a graded spectrum rather than a binary trait. Leading science journals have been adopting this relativist view, thereby opposing fundamental biological facts. While we fully endorse efforts to create a more inclusive environment for gender‐diverse people, this does not require denying biological sex. On the contrary, the rejection of biological sex seems to be based on a lack of knowledge about evolution and it champions species chauvinism, inasmuch as it imposes human identity notions on millions of other species. We argue that the biological definition of the sexes remains central to recognising the diversity of life. Humans with their unique combination of biological sex and gender are different from non‐human animals and plants in this respect. Denying the concept of biological sex, for whatever cause, ultimately erodes scientific progress and may open the flood gates to "alternative truths." Abstract : Leading science journals increasingly adopt a view considering sex as a graded spectrum rather than binary. Thereby, they confuse operational definitions of sex, sexual differentiation, and variable sex roles with biological sex, which simply distinguishes two reproductive strategies, a female one producing large gametes, and a male one producing small gametes.